Illuminating Epigenetics and Inheritance in the Immune System with Bioluminescence. Issue 11 (November 2020) - Dimond, Andrew; Van de Pette, Mathew; Fisher, Amanda G.
Abstract : The remarkable process of light emission by living organisms has fascinated mankind for thousands of years. A recent expansion in the repertoire of catalytic luciferase enzymes, coupled with the discovery of the genes and pathways that encode different luciferin substrates, means that bioluminescence imaging (BLI) is set to revolutionize longitudinal and dynamic studies of gene control within biomedicine, including the regulation of immune responses. In this review article, we summarize recent advances in bioluminescence-based imaging approaches that promise to enlighten our understanding of in vivo gene and epigenetic control within the immune system. Highlights: BLI is a powerful technique for non-invasive visualization of in vivo processes, with key advantages being its low background and high sensitivity. BLI can be used to study dynamic gene expression and epigenetic changes in vivo, with increasing opportunities for applying this imaging approach more widely in immunology. Technological advances are expanding the toolkit of luciferases and substrates available for BLI, such as by enabling deeper visualization and dual-reporter imaging. Newly characterized bioluminescent systems are opening the possibility of engineering autonomously bioluminescent organisms, potentially revolutionizing the field of in vivo BLI. Recent advances in genome-editing tools are rendering the insertion of reporters into endogenous loci to generate new and better transgenic models for BLI widely feasible.